(Auto)analityczny opis przypadku. Wspomnienia Izydora Sadgera o Zygmuncie Freudzie - Więckiewicz, Agnieszka (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The article presents an analysis of Freud’s early biography written by Isidor Isaak Sadger, one of his earliest students. The author argues that Sigmund Freud. Persönliche Erinnerungen bonds together different literary genres such as biography, autobiography and pathography, thus allowing for studying the impact of life-writing literature on psychoanalysis. The first part of the article is devoted to the relation between introspection, auto-analysis and everyday writing practices of Freud and his students. In the second part, the author presents unknown facts from Sadger’s history in the psychoanalytic movement and reads his biography as an example of a heterogeneous literary genre where he becomes a writer-biographer and a doctor-autobiographer simultaneously.